PENGARUH BIOCHAR SEKAM PADI DOSIS TINGGI TERHADAP SIFAT FISIK TANAH DAN PERTUMBUHAN TANAMAN JAGUNG PADA TYPIC KANHAPLUDULT - Syafitri Dewi Widyantika; Sugeng Prijono (Jurnal Tanah dan Sumberdaya Lahan, 2019)
Typic Kanhapludult is an acid dry soil which has soil pH of less than 5,5, low orgaic matter (<1%), bulk density of more than >1,3 g cm-3, low total pore space, and low pore water, that are not optimal for supporting plant growth. Provision of biochar to the soil can increase soil organic matter content for improving soil physical properties and plant growth. The objectives of this study that was conducted in the glasshouse of Indonesian Soil Research Institute, was to quantify the effect of rice husk biochar on some of soil physical properties, and vegetative growth of maize in a Typic Kanhapludult. The results showed that application of biochar with high doses significantly decreased soil bulk density, increased total pore space, and increased available water pores. Application of rice husk biochar had no significant effect on permeability, as well as rapid drainage pore, and slow drainage pore. Provision of rice husk biochar with higher doses than control on Typic Kanhapludult that improved soil physical properties improved vegetative growth of maize as shown by significant increases in plant height, fresh biomass and dry biomass of the crop.